Pembangunan Interior Perlengkapan Kapal Riset POLBENG 1 - Purwoko , Muhammad Sidik; Suranto, Maful; Fazrian; Purwoko, Muhammad Sidik (P3M Politeknik Negeri Bengkalis, 2025)
Planning a ship's interior is much the same as planning the interior of any other land-based structure. One thing that distinguishes ships is their corrosive environment due to large waves, storms, and other external disturbances. The shape of the space also distinguishes them, such as the distinctive ship shape, small or confined spaces, and sometimes even more irregular shapes such as curved ones. Narrow or confined spaces may be necessary in certain situations to meet the needs of the crew or passengers for living, working, and resting during voyages, which can sometimes last for long periods, even months. Therefore, the interior spaces of a ship must meet the aforementioned requirements.